2017
DOI: 10.1007/s00253-016-8071-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel scalable, robust downstream process for oncolytic rat parvovirus: isoelectric point-based elimination of empty particles

Abstract: The rodent protoparvovirus H-1PV, with its oncolytic and oncosuppressive properties, is a promising anticancer agent currently under testing in clinical trials. This explains the current demand for a scalable, good manufacturing practice-compatible virus purification process yielding high-grade pure infectious particles and overcoming the limitations of the current system based on density gradient centrifugation. We describe here a scalable process offering high purity and recovery. Taking advantage of the iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In our process, the majority of infective virus particles are cell-associated at the time of harvest. To harvest H-1PV, a freeze–thaw cell lysis in Tris–EDTA buffer (VTE) (Leuchs et al, 2016 ) or Tris–HCl buffer (VT) (Leuchs et al, 2017 ) was previously reported for stationary cultures. For large-scale production with adherent cells on carriers, a scalable cell lysis is required.…”
Section: Resultsmentioning
confidence: 99%
“…In our process, the majority of infective virus particles are cell-associated at the time of harvest. To harvest H-1PV, a freeze–thaw cell lysis in Tris–EDTA buffer (VTE) (Leuchs et al, 2016 ) or Tris–HCl buffer (VT) (Leuchs et al, 2017 ) was previously reported for stationary cultures. For large-scale production with adherent cells on carriers, a scalable cell lysis is required.…”
Section: Resultsmentioning
confidence: 99%
“…The rodent protoparvovirus H-1 is currently in Phase I/IIA clinical trials against glioblastoma [ 214 , 215 ] and pancreatic cancer [ 216 ] in Germany. Viral capsids are non-enveloped and extremely rugged, simplifying their production, purification and storage [ 217 219 ], as well as enhancing their tissue penetration properties. The protoparvoviruses belong to the same virus family as the adeno-associated viruses (AAV), which have already found extensive clinical use as gene therapy vectors.…”
Section: Box 2 Case Examples: Rodent Protoparvovirusesmentioning
confidence: 99%
“…Selectivity is described frequently as correlating with protein isoelectric (pI) point [12][13][14][15][16] . Differences in pI have been documented among full and empty capsids for several parvoviruses, including AAV [17][18][19][20][21] but descending pH gradient elution has not proven effective for separating their empty and full capsids. A comprehensive study with structurally-similar minute virus of mice (MVM) showed that selectivity was dominated by the distribution of charges on capsid surfaces rather than their net charge [20] .…”
Section: Introductionmentioning
confidence: 99%